The Impact of Internet of Things Devices on Women’s Educational Access and Safety in Digital Environments - Masoumeh Ganjizadeh; Usman Quraishi; Tayeba Amir; Quraishi, Tamanna; Mitra Ahmadi (International Journal of Global Sustainable Research, 2025)
This study investigates the role of Internet of Things (IoT) devices in enhancing women's safety and access to education, particularly in virtual university environments. It aims to assess the effectiveness of IoT tools like panic buttons and tracking systems in online learning settings. A mixed-methods approach was used, surveying 130 students across disciplines such as computer science, medicine, education, and economics. Results show that most participants view IoT devices as highly effective in improving women’s safety and would recommend their use in educational contexts. The study concludes that IoT solutions can strengthen women’s security and empowerment in digital education spaces, contributing valuable insights to the evolving field of technology-enabled education for women's advancement